Unregulated Cryptocurrency: Need for Legal Regulation in Digital Economy - Makhija , Rashi (Trinity Law Review, 2024)
This research paper explores the intricate relationship between cryptocurrency  law and the broader economic payment landscape. Cryptocurrencies, powered  by blockchain technology, have emerged as a transformative force in financial  systems globally. The regulatory frameworks governing this non legal tender vir tual currency play a pivotal role in shaping their adoption, market dynamics, and  impact on traditional economic structures. This article also delves into the diverse  approaches taken by governments worldwide in regulating cryptocurrencies.  It examines the challenges and significances presented by this decentralized finan cial paradigm. Furthermore, the paper explores the economic implications of  cryptocurrency regulation. It explores how regulatory clarity or ambiguity affects  investor confidence, market liquidity, and the ability of these digital assets to serve  as alternative forms of currency or investment. The interplay between taxation  policies, anti-money laundering measures, and the growth of the cryptocurrency  ecosystem is examined to understand their combined impact on economic devel opment. Through an interdisciplinary lens, this research article aims to contribute  insights into the evolving dynamics of cryptocurrency law and its influence on the  broader economy which can lead to heavy scams.
Keywords: Economic; Bank; Currency; Cryptocurrency and Government